A tour of Luther’s Works - Lazcano, Rafael (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2019)
Martin Luther’s work was rooted in cultural, social and economic factors, reached maturity in the High Middle Ages, and provided fertile ground for the proclamation, geographical expansion and doctrinal development of the Protestant Reformation. Trapped by the word of God, Luther, a man of simple and sincere faith, discovered a new way of relating to God by sola fide, sola gratia, and sola Scriptura, faced with the justification/salvation of the human being. This unique discovery defeated the doctrine of the medieval Catholic church, the pope and ecclesiastical hierarchies, indulgences, relics and saints, celibacy and monastic life. Like wise, Luther through the strength of his Word opened up a horizon of freedom for human life and society, a new way of accessing the world and society, which would guide the trajectory taken by humans and modernity to this day.